Large eddy simulations of flow over solid circular cylinders and rectangular blocks - Lim, Yong Xiang (2016)
Due to the rising need to understand flow across circular cylinders, many investigations have been conducted in the past. The aim of the current work was to investigate the influence of various parameters by conducting three dimensional numerical simulations for flow across a circular cylinder. By obtaining the drag and lift coefficients, the effect of different Reynolds number and number of cells would be compared. This simulation was done using Large Eddy Simulation. By comparing the results of Re=3900 to various published results, LES was proved to show good agreement with the other papers. Therefore, LES could be used for further investigations of higher Reynolds numbers especially those in supercritical and transitional region. Simulations using LES were also conducted for rectangular blocks to compare results with previous experiments. The results also showed that LES was proved to be in good agreement with other papers. Therefore, LES modeling was proven to be a very powerful and useful tool for numerical simulations.